SOCIAL MEDIA AND ONLINE FOOD DELIVERY BASED DIGITAL MARKETING STRATEGY FROM AN ISLAMIC ECONOMICS PERSPECTIVE: A CASE STUDY OF BAKSO PRESIDENT MALANG - Eka Aprilia Dewitasari; Moh. Mukhsinin Syu'aibi; Muhammad Fahmul Iltiham (Jurnal Dinamika Ekonomi Syariah, 2026)
Rapid advancements in digital technology have fundamentally reshaped the way businesses operate and compete, particularly within the food and beverage sector. This study investigates how Bakso President Malang well established local meatball restaurant has leveraged digital marketing strategies through social media and online food delivery platforms to expand its customer base and improve overall sales performance. Employing a qualitative descriptive method with a case study design, data were gathered through direct observation, in-depth interviews with the business owner, and relevant documentation. The results demonstrate that active engagement on Instagram and TikTok, combined with registration on GoFood, GrabFood, and ShopeeFood, has meaningfully broadened the business's market reach and driven transaction growth. Key enabling factors include the restaurant's strong local reputation, its distinctive setting near a railway track, and a dedicated digital content management team. However, several constraints were also identified, namely high platform commission rates, limited digital marketing expertise among staff, and the lack of a structured content planning system. From an Islamic economics standpoint, the arrangement between the business and digital platforms aligns with the principles of the ijarah contract characterized by mutual willingness, clearly defined service objects, and transparent compensation terms. This study offers practical guidance for culinary SMEs seeking to integrate digital tools into an ethically grounded and sustainable business model